Stress hyper-reactivity increases vulnerability to developing binge-type eating and associated anxiety-like behavior; comparison between Wistar-Kyoto and Sprague-Dawley rats - Rodríguez-Rangel, Daniela Sarai; Estrada-Camarena, Erika; López-Rubalcava, Carolina (Frontiers in Nutrition, 2024)
Binge eating disorder (BED) is a widespread eating disorder that primarily affects women worldwide, and it is characterized by the presence of binge eating episodes and the absence of any compensatory behavior to prevent weight gain. BED presents elevated comorbidity with other psychiatric disorders, such as anxiety, and it has been suggested that stress sensibility could be a vulnerability factor for the development of BED and the associated anxiety comorbidity. In this study, we aim to investigate whether the Wistar-Kyoto rat strain (WKY), which has a stress hyperreactive phenotype, could develop both binge-type eating and anxiety-like behaviors simultaneously. We also aim to compare its vulnerability to developing both behaviors with the Sprague Dawley rat strain (SD), a rat strain commonly used in binge-eating models. For this purpose, rats were subjected to the model of intermittent access to palatable food (sucrose solution 30% or shortening) without calorie restriction or stress exposure. We evaluated and compared the development of binge-type eating behavior, anxiety-like behavior, and serum corticosterone variation as an index of the stress response in both rat strains. Results showed that WKY rats presented a higher percentage of bingetype eaters and required less time to develop binge-type eating behavior than SD rats. The WKY eating pattern emulated a binge-eating episode regardless of the palatable food. Although the development of sucrose binge-type eating was similar between strains, WKY developed more easily the shortening binge-type eating than SD and was more susceptible to developing anxiety-like behavior. Additionally, sucrose binge eating seems to differentially affect both strains' hypothalamic-pituitary-adrenal (HPA) axis response to stress since it facilitated its response in SD and blunted it in WKY. In conclusion, results showed that a hyper-reactive stress phenotype predisposes the development of binge-type eating behavior and anxiety-like behavior in the absence of calorie restriction and stress exposure.